Hollywood's artists : the Directors Guild of America and the construction of authorship - Wexman, Virginia Wright (Film and culture., 2020)
"The production of a Hollywood movie encompasses the work of many people from the screenwriter and editor to the cinematographer and boom operator. Yet it is the director who is considered the artistic force behind a film. The notion of the director as the author of a film was not always a given but the result of a variety of different historical and institutional factors, including the breakup of the classical Hollywood studio system and the rise of the auteur theory in the 1960s. An often overlooked player in this story is the Directors Guild of America (DGA) that, as Virginia Wright Wexman argues, played a crucial role in establishing the director's status and power in Hollywood and in the public's mind. In Hollywood's Artists, Wexman provides the first history of the DGA and its influence. She begins by discussing how it differentiated itself from other industry unions, focusing on issues of status, networking, and creative control as opposed to money and job security. Wexman then considers how the DGA fought for directors to be credited as "authors" of the film and how this put them in conflict with others in the film industry. In addition to tracing the history of how directors created their image in the public's imagination, including their role in the McCarthy hearings, Wexman discusses how the DGA fought to have directors get more legal control over their films"--